2019
DOI: 10.6018/analesps.35.3.320441
|View full text |Cite
|
Sign up to set email alerts
|

Motivational profiles related to the academic satisfaction of university students

Abstract: Los objetivos del estudio fueron identificar los perfiles motivacionales de estudiantes universitarios y evaluar sus diferencias en cuanto a la satisfacción académica. Los participantes fueron 882 estudiantes con edades comprendidas entre los 17 y 50 años, procedentes de nueve universidades chilenas. Los perfiles motivacionales se identificaron mediante análisis de conglomerados, siguiendo la combinación de métodos jerárquicos y no jerárquicos. El análisis de conglomerados se realizó incluyendo las siguientes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
1
3
0
7
Order By: Relevance
“…Based on the first of the proposed objectives, to analyze the motivational profiles that might exist in a sample of PE students, four types of motivational profiles were found. These results are in line with those found by Sánchez-Oliva et al [32] in a sample made up of 1690 students and Manzano-Sánchez et al [9] with 768 students, both groups with a mean age of 13, while Vergara-Morales et al [14] found these same profiles among university students. However, results indicate no agreement with studies such as the one by Moreno et al [52] who found three profiles, Haerens et al [53] with five profiles, and Valle et al [13], six profiles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on the first of the proposed objectives, to analyze the motivational profiles that might exist in a sample of PE students, four types of motivational profiles were found. These results are in line with those found by Sánchez-Oliva et al [32] in a sample made up of 1690 students and Manzano-Sánchez et al [9] with 768 students, both groups with a mean age of 13, while Vergara-Morales et al [14] found these same profiles among university students. However, results indicate no agreement with studies such as the one by Moreno et al [52] who found three profiles, Haerens et al [53] with five profiles, and Valle et al [13], six profiles.…”
Section: Discussionsupporting
confidence: 91%
“…Motivation has been studied through motivational profiles employing a cluster analysis from different approaches, such as in the field of PE [7][8][9], sports [5,10,11] and university students [12][13][14], among others. SDT encompasses, in turn, the Basic Psychological Needs (BPN) theory, which highlights the presence of three psychological needs: competence (focused on mastery of skills), autonomy (oriented to the development of good actions) and relationship (aimed at connecting and giving affection to others) which, when developed, promote progress in motivation [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the same line of thought as the previous author, in the study of [10], it is pointed out that the context of the pandemic has not only made the existing deficiencies and major inequities more noticeable, which already made it difficult to achieve the achievement of competencies in the university students in the faceto-face context, has also brought to light the deficiencies of acquiring these skills through virtual environments.…”
Section: Introductionmentioning
confidence: 76%
“…Otra de las variables relevantes para el ajuste es la motivación, definida como aquellas fuerzas percibidas que mueven a la persona a actuar, se enfoca en los procesos internos que las llevan a actuar (Ryan y Deci, 2019;Stover et al, 2017). En términos educativos, reside en el tipo de motivación que el estudiantado emplea para el logro de sus metas académicas (Vergara-Morales et al, 2019).…”
Section: Motivación Académicaunclassified